Strategy The principal's Leadership Style in Implementing “Merdeka Belajar” in Schools - Mastur Mastur (Kelola: Jurnal Manajemen Pendidikan, 2023)
Curriculum changes are part of improving the existing education system in Indonesia. Principal leadership has an important role and position in achieving educational goals. This study aims to discuss the principal's leadership style in implementing "merdeka belajar" in schools. This research uses the literature study method, which collects materials from books, journals, articles, and other sources related to the principal's leadership strategy in realizing Independent Learning in schools. The study results show that implementing the independent curriculum makes teachers more professional through various coaching and training. The principal carries out his role as a mediator and motivator for teacher participation in curriculum training. The principal also acts as a participant in regular meetings or discussions. The principal also supervises evaluators in implementing the independent curriculum. The factor faced by school principals is the lack of smoothness of the internet network as a means for teachers to use technology in learning. School principals consider the expected results of the theories in the research in making decisions to answer problems and improve the quality or quality of education by implementing an independent curriculum.